OWNERSHIP STRUCTURES AND DIVIDEND POLICY IN MANUFACTURING COMPANIES IN INDONESIA - Ida Setya Dwi Jayanti; Ayu Febriyanti Puspitasari (TIJAB (The International Journal of Applied Business), 2017)
This study aims at examining the influence of ownership structure on dividendpolicy. The population is all of manufacturing companies listed on Indonesia Stock Exchange for the period 2008–2012. Purposive sampling is used to choose the sample and 81 companies are found to be sample. The study uses multiple linear regression. The result shows that managerial ownership, institutional ownership, foreign ownership, ownership concentration, and the control variable free cash flow simultaneously have significant influence on dividend policy. Influence testing partially by the level of significant of 5% shows that managerial ownership has positive and significant influence on dividend policy, institutional ownership has insignificant influence on dividend policy, foreign ownership has insignificant influence on dividend policy, ownership concentration has positive and significant influence on dividend policy, and the control variable free cash flow has positive and significant influence on dividend policy.